The Practicality of Popular Scientific Books based on the Diversity of Fish Species in Puting River Waters - Iim Mahayu Buana Kusuma Rini; Muhammad Zaini; Danang Biyatmoko (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Teaching materials are needed to assist in the learning process. One of the teaching materials that can be used is in the form of popular scientific books. Popular scientific books developed must be based on local potential to support learning the concept of diversity in animal ecology courses. So the purpose of this development research is to get the results of the practicality of the contents and expectations of the prototype of a popular scientific book with the title "Diversity of Fish Species in Puting River Waters". The BIP development method uses a development research design model from Tessmer which focuses on formative evaluation. The results of the research on the content practicality test obtained an overall percentage average value of 91.67% with very good criteria, while the results of the expected and actual practicality test were seen from the results of the implementation of popular scientific books which obtained an average of 82.41% with very good criteria, and the results of student responses to popular scientific books obtained an average of 91.97% with the criteria of strongly agreeing. This proves that a popular scientific book with the title "Diversity of Fish Species in Puting River Waters" is very practical to use to explore students' critical thinking skills in learning Animal Ecology.AbstrakBahan ajar diperlukan untuk membantu dalam proses pembelajaran. Salah satu bahan ajar yang dapat digunakan yaitu berbentuk buku ilmiah populer. Buku ilmiah populer yang dikembangkan harus berbasis potensi lokal untuk menunjang pembelajaran konsep keanekaragaman pada mata kuliah ekologi hewan. Maka tujuan penelitian pengembangan ini adalah untuk mendapatkan hasil kepraktisan isi dan harapan prototipe buku ilmiah populer dengan judul “Keanekaragaman Jenis Ikan di Perairan Sungai Puting”. Metode pengembangan BIP menggunakan model desain penelitian pengembangan dari Tessmer yang berfokus pada evaluasi formatif. Hasil penelitian pada uji kepraktisan isi memperoleh nilai rata-rata persentase  keseluruhan sebesar 91,67% dengan kriteria sangat baik, sedangkan  hasil uji kepraktisan harapan dan aktual dilihat dari hasil uji keterlaksanaan buku ilmiah populer yang memperoleh rata-rata 82,41% dengan kriteria sangat baik dan hasil respon mahasiswa terhadap buku ilmiah populer memperoleh rata-rata 91,97% dengan kriteria sangat setuju. Hal tersebut membuktikan bahwa buku ilmiah populer dengan judul “Keanekaragaman Jenis Ikan di Perairan Sungai Puting” sangat praktis digunakan untuk menggali keterampilan berpikir kritis mahasiswa dalam pembelajaran Ekologi Hewan.